Investigation of the sequential accelerator on the perceptron for pattern recognition - Sirote Saetang. (2013)
Machine Learning methods have been widely used in recent years in many areas, such as object recognition, autonomous vehicle, recovery rate of symptoms and stock prediction. However, it is very difficult task to make a computer learn from experience as human can. Machine learning has been in the field of research for more than five decades since 1950s. It has become a challenging task to create the method that able to make machines can learn faster.